Fabrication Long Period Fiber Bragg Grating Based on Photonic Crystal Fiber Using CO2 Laser - Mahgoob, Nidaa L.; Al-Dergazly, Anwaar A. (Al-Nahrain Journal for Engineering Sciences, 2025)
Photonic crystal fibers (PCFs) are generally divided into two categories: solid-core photonic crystal fibers and hollow-core photonic crystal fibers. In this paper, a long-period fiber Bragg grating (LPFBG) was experimentally fabricated in a hollow-core photonic crystal fiber (HC-PCF) using a CO₂ laser and based on the point-by-point technique. Proper LPFBGs were inscribed using laser powers of 0.9 W and 1.4 W, with grating parameters (grating period, length of each pitch, and depth of each pitch) equal to (136 µm, 48.042 µm, 16 µm) and (142 µm, 74.027 µm, 22.09 µm), respectively, for two samples. The Bragg wavelengths and full-width at half-maximum (FWHM) were (1529.274 nm, 1.34 nm) and (1529.629 nm, 5.11 nm), respectively, for the two samples fabricated using CO₂ laser powers of 0.9 W and 1.4 W. From these results, it was recognized that the optimal LPFBG-HC-PCF was the one fabricated using 0.9 W laser power. The unique structure of hollow-core photonic crystal fibers, which enables light propagation within the air core and provides a large internal surface area, has attracted significant research interest for various sensing و communication applications, Environmental and Biological Monitoring, and medical applications.